Laboratory manual in fundamentals of entomology - Ibrahim, Yusof (Universiti Putra Malaysia Press, 2011)
Entomology is a biological science dealing generally with anthropods and specifically insects. Agricultural entomology is a branch of entomology that deals with anthropods which effect the welfare of men, his crops and domesticated animals, either through their direct attacks, through their ability to transmit causal agents of diseases, or as a result of harmful effects from direct contacts. This manual on the fundamentals of entomology has been written to provide practical knowledge necessary for a beginner and those who may never again have a laboratory exercise in general biology. For those who plan to major in entomology, this manual will provide sufficient background in important phases of entomology adequate to cope with the future and more specialized subjects.